Skill Disparities and Unequal Family Outcomes - Shelly Lundberg (Institute for the Study of Labor (IZA), 2014)
The prevalence and stability of marriage has declined in the United States as the economic lives of men and women have converged. Family change has not been uniform, however, and the widening gaps in marital status, relationship stability, and childbearing between socioeconomic groups raise concerns about child wellbeing in poor families and future inequality. This paper uses data from a recent cohort of young adults Wave IV of the National Longitudinal Study of Adolescent Health to investigate whether disparities in cognitive ability and non-cognitive skills contribute to this gap. Blinder-Oaxaca decompositions of differences in key family outcomes across education groups show that, though individual non-cognitive traits are significantly associated with union status, relationship instability and single motherhood, they collectively make no significant contribution to the explanation of educational gaps for almost all of these outcomes. Measured skills can explain as much as 25 percent of differences in these outcomes by family background (measured by mother's education), but this effect disappears when own education is added to the model. Both cognitive and non-cognitive skills are strongly predictive of education attainment but, conditional on education, explain very little of the socioeconomic gaps in family outcomes for young adults.
Keywords: I24; J12; J24; 330; cognitive ability; non-cognitive skills; family; marriage; inequality